Prevalence and Incidence of Non-neutralizing Antibodies in Congenital Hemophilia A— A Systematic Review and Meta-Analysis - Abdi, A.; Bordbar, M. R.; Hassan, S.; Rosendaal, F. R.; van der Bom, J. G.; Voorberg, J.; Fijnvandraat, K.; Gouw, S. C. (Frontiers in Immunology, 2020)
Objectives: In hemophilia A the presence of non-neutralizing antibodies (NNAs) against Factor VIII (FVIII) may predict the development of neutralizing antibodies (inhibitors) and accelerate clearance of administrated FVIII concentrates. This systematic review aimed to assess: 1) the prevalence and incidence of NNAs in patients with congenital hemophilia without inhibitors and 2) the association between NNAs and patient and treatment characteristics. Methods: We conducted a search in MEDLINE, Embase, Web of Science and the Cochrane database. We included cross-sectional and longitudinal studies reporting on NNAs in patients with hemophilia A and B, who were inhibitor-negative at the start of the observation period. Data were extracted on: hemophilia type and severity, patient and treatment characteristics, NNA prevalence and incidence, NNA assays and inhibitor development. Two independent reviewers performed study selection, data extraction and risk of bias assessment, using adapted criteria of the Joanna Briggs Institute. Studies were classified as high-quality when ≥5/9 criteria were met. NNA assays were classified as high-quality when both quality criteria were met: 1) use of positive controls and 2) competition with FVIII to establish FVIII-specificity. We reported NNA prevalence and incidence for each study. The pooled NNA prevalence was assessed for well-designed studies in previously treated patients, employing high-quality NNA assays. Results: We included data from 2723 inhibitor-negative patients with hemophilia A, derived from 28 studies. Most studies were cross-sectional (19/28) and none reported on NNAs in hemophilia B. Study design was of high quality in 16/28 studies and the NNA assay quality was high in 9/28 studies. Various NNA assays were used, predominantly ELISA (18/28) with different cut-off values. We found a large variety in NNA prevalence (Range, 0-100%). The pooled NNA prevalence in high-quality studies was 25% (95%CI, 16-38%). The incidence of new NNA development was reported in one study (0.01 NNA per person-exposure day). Conclusion: This systematic review identified studies that were heterogeneous in study design, patient population and NNA assays type, with NNA prevalence ranging from 0-100% in inhibitor-negative patients with hemophilia A. The pooled NNA prevalence was 25% in high-quality studies including only previously treated patients and performing high-quality NNA assays.